Potrzeby informacyjne współczesnego controllingu - Chachuła, Dagmara (Informative Needs of Controlling, 2005)
This article presents internal and external needs of Controlling and focus mainly on accouting as a main source of informative system for Controlling. Accounting can offer many Instruments which can be used by controlling in the process od acquiring information. Whithout instruments, which were presented in this paper, controlling system could not exist. This article also tries to settle the problem of relationship between accounting and controlling and gives an answer to the question what is the percentage accounting share in controlling.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 102-111